Relationship between psychological contract fulfillment, job burnout, and job satisfaction among pharmacists in private medical institutions in Guiyang, China - Ting Zhang; Man Ao; Lei Lu; Shuya Chen; Yongyong Luo; Yongyong Luo; Yongyong Luo; Fushan Tang; Fushan Tang; Fushan Tang (Frontiers in Public Health, 2025)
ObjectiveThis research aims to systematically investigate the mechanisms between psychological contract fulfillment and job burnout/job satisfaction among pharmacists, addressing the research gap in this population.MethodsThis is a cross-sectional research that employed convenience sampling to recruit 384 pharmacists from private medical institutions in Guiyang between May and August 2024. The research utilized scales for psychological contract, job burnout, and job satisfaction for analysis. After conducting reliability and validity tests on the questionnaires, correlation analysis, mediation analysis, and multiple linear regression analysis were employed to explore the relationships among psychological contract fulfillment, job burnout, and job satisfaction among pharmacists in private medical institutions.ResultsThe findings indicate that pharmacists’ psychological contract fulfillment is significantly weakly negatively correlated with job burnout (r = −0.187, p < 0.01) and significantly strongly positively correlated with job satisfaction (r = 0.528, p < 0.01), and a significant strongly negatively correlation between the job burnout and the job satisfaction (r = −0.436, p < 0.01). Mediation analysis shows that job burnout plays an weakly mediating role in the relationship between psychological contract fulfillment and job satisfaction (12.16%, p < 0.01). This suggests that burnout is merely a minor component within a much broader context. In addition, a considerable proportion of pharmacists 43.23% indicated that their level of psychological contract fulfillment did not meet the benchmark value (most of the responsibility has been fulfilled). indicating significant psychological contract breaches within this group. Multiple linear regression analysis further identifies that demographic variables (age, employment length), psychological contract fulfillment, and burnout levels collectively serve as core predictors of job satisfaction.ConclusionThe research suggests that private medical institutions should take proactive measures to ensure the stability of pharmacists’ psychological contracts. For example, during the intervention process, preventive guidance should be provided to senior pharmacists to help them avoid breaches of the psychological contract and the further development of job burnout. For newly recruited pharmacists, selective preventive interventions should be implemented to achieve personalized psychological contract interventions. Finally, this research helps fill the research gap regarding pharmacists’ psychological contracts in private medical institutions.